Lidské určení jako problém definice člověka ve filosofické antropologii - Marek, Jakub (Lidé města, 2007)
This article tentatively dissects the basic problems of philosophical anthropology that call for more thorough and more consistent treatment in the future. In the first section the article tracks the problem of anthropology as an integral science of man which deals with problem of human objectivity and one’s subjectivity. It is followed by focusing on philosophical anthropology showing it in three different specific forms, as a “general science”, “universal treatment”, and “prophetic philosophy”. The crucial basic problem is from which angle and with which claim it is applied in outlining the philosophical anthropology and what are its limits. The second section is devoted to the actual “destiny of humanity” as the basic problem of philosophical anthropology reflecting primarily how is this topic addressed by Max Scheler and Arnold Gehlen, two representatives of more detailed understanding of philosophical anthropology. The question of subjectivity as a focal point of understanding the very humanity of a individual human being is finally followed form the perspective of Kierkegaard's spirit determination.